Change of mortality of patients with acute ischemic stroke before and after 2015 - Park, Sang-Won; Lee, Ji Young; Heo, Nam Hun; Han, James Jisu; Lee, Eun Chae; Hong, Dong-Yong; Lee, Dong-Hun; Lee, Byung Cheol; Lim, Young Wha; Kim, Gui Ok; Lee, Man Ryul; Oh, Jae Sang (Frontiers in Neurology, 2022)
Introduction Advances in the diagnosis and management of acute ischemic stroke (AIS) and the increased use of mechanical thrombectomy (MT) have improved the quality of care and prognosis of patients with AIS since 2015. We investigated the changing trends in mortality of patients with AIS in Korea before and after 2015. Materials and methods A retrospective cohort study was conducted using combined anonymized data from the Acute Stroke Assessment Registry of Korea and the Health Insurance Review & Assessment Service database. Patients with ischemic stroke with precise onset time and initial National Institute of Health Stroke Scale records were included. Results Patients receiving MT treatment increased from 256 (2.7%) pre-2015 to 1,037 (3.9%) post-2015 (p < 0.001). Overall mortality significantly decreased from pre-2015 to post-2015. In pre-2015, intravenous thrombolysis (IVT) administered within 2 h significantly reduced 3-month mortality when compared with non-IVT. While, in post-2015, IVT administered within 2 h significantly reduced the 3-month, 1-year, 2-year, and 4-year mortality (p < 0.05). MT only reduced 1-year mortality pre-2015; however, MT significantly reduced the 3-month, 1-year, and 2-year mortality post-2015 (p < 0.05). Post-stroke antiplatelet and anticoagulant drugs significantly reduced the 3-month, 1-year, 2-year, and 4-year mortality post-2015. Discussion Since 2015, faster IVT has significantly reduced the short- and long-term mortality in patients with AIS; MT reduced the 3-month, 1-year, and 2-year mortality. Post-stroke antithrombotic medication has significantly lowered the 2- and 4-year mortality since 2015. Conclusions Changing trends in AIS management since 2015 have improved the prognosis of patients with AIS.